A Study of The Compelling Role of Language in Influencing Culture and Community - Md. Mahmud Hasan Chowdhury; Md. Sabbir Hossain (CV. Eureka Murakabi Abadi, 2022)
Language works as a gateway to express one's entire feelings or emotions. By using the dynamic force of the language, everyone reflects the culture of the community to which they belong. That means there lies a close connection between language and the culture of a community. Generally, each language represents a definite culture and a community. Likewise, the language of Bangladesh represents the cultural standard of the communities that belong to it. Thus, to show the immense influence of language on culture and the community, the researchers have selected a specific region of Bangladesh from the perspective of cultural and linguistic diversity. In this study, the researchers have used a descriptive research design and mixed methods following both quantitative and qualitative approaches to inquire appropriately. They have also used questionnaires to explore the dynamic force of language in both the culture and the community. The result of the present inquiry opines that language plays as a driving force in the culture of people of different ethnicities. In addition, this study also illuminates that the modification of language plays a significant role in modifying the style of living of a group of people, and gradually they lose their uniqueness and get accustomed to practicing different cultures subconsciously. It can be concluded that this research is to reveal the implicit propriety of language, which has the power to reshape the culture and the fundamental fabrics of the community